ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PERUBAHAN PROFITABILITAS PERUSAHAAN PASCA PENAWARAN SAHAM PERDANA - Nadin, Muhammad Audi De; T, Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aimed at examining the difference in corporate profitability between pre- and post-initial public offering (IPO) and focused on the effect of ownership structure toward profitability change. Samples of this research were firms conducting IPO on Bursa Efek Indonesia (BEI) from 2009-2011, not financial firms nor banking firms, and providing Â necessary information for this current research. Setting those criteria, 52 companies met the criteria to be taken as samples of this research. This research was conducted by means of comparing the average profitability of the firms for the period before and after the IPO and using multiple linear regression test. This research revealed the decline in post-issue firm profitability, which was one year before IPO and two years after IPO, measured by return on equity (ROE), return on asset (ROA), operating income to asset (OI/A) and, sales to asset (S/A). This research further found that the change of post-issue profitability was not associated with ownership structure. The portion of institutional ownership, public ownership, and existence of managerial ownership did not affect the change of post-issue firm profitability. Â Keywords: Initial public offering, profitability, return on equity (ROE), return onÂ asset (ROA), operating income to asset (OI/A), sales to asset (S/A), ownership structure, institutional ownership, public ownership, managerial ownership